INTRA-ABDOMINAL HYPERTENSION SYNDROME AFTER REMOVAL OF LARGE AND HUGE POSTOPERATIVE VENTRAL HERNIAS - A. L. Zhulyev; B. A. Isaychev; D. B. Dyomin (Acta Biomedica Scientifica, 2012)
23 patients operated on account of large and huge postoperative ventral hernias were examined. It was revealed that in spite of preventive measures realized before the operation the increase of intra-abdominal pressure was registered in 34,8 % of cases. Manifestations of intra-abdominal hypertension syndrome appeared in 26 % of patients. Significant connection between the sized of hernial outpouching, diameter of hernial gates and. the level of intra-abdominal hypertension and. also frequency of intra-abdominal hypertension syndrome that testifies to the expediency of search of new ways to prevent development of this postoperative complication. Key words: postoperative ventral hernia, intra-abdominal hypertension syndrome